Assessing the quantum yield spectrum of photochemically produced reactive intermediates from black carbon of various sources and properties. (1st February 2023) - Wang, Yanling; Wu, Binbin; Zheng, Xiaoshan; Chen, Baoliang; Chu, Chiheng
Highlights: We report the quantum yield (QY) spectrum of PPRIs from black carbon (BC). PPRIs QYs from BC are highly dependent on pyrolysis temperature and size. BC from different biomasses display unexpected small variation in PPRIs QYs. Optical and surface redox characteristics of BC determines PPRIs QYs. Abstract: Black carbon (BC) is ubiquitous in sunlit waters and atomosphere. Recent studies revealed that under sunlight irradiation BC is photoactive on producing photochemically produced reactive intermediates (PPRIs), a group of key species in accelerating earth's surface biogeochemical processes and pollutant dynamics. Nevertheless, reported PPRIs productions from BC exhibit large inconsistency and the intrinsic capacities of BC in producing PPRIs remain poorly characterized. This work provided a wavelength-dependent quantum yields (QYs) assessment of four environmentally-relevant PPRIs (excited triplet state BC ( 3 BC*), singlet oxygen ( 1 O2 ), hydrogen peroxide (H2 O2 ), and hydroxyl radical ( · OH)) from various BC. The QYs of all investigated PPRIs exhibit high dependence on incident light wavelength. For instance, the QYs of 1 O2 dramatically decreased from 4.4% to 0.4% with light wavelength increasing from 375 to 490 nm and decreased to 0 above 490 nm. Suprisingly, PPRIs QYs only varied by 2.0–2.5-fold among BC prepared from different biomasses (i.e., pine needle, shell, straw, and wood), while the pyrolysis temperature and size of BC demonstrate higher impacts on the PPRIs QYs by up to 30.3- and 7.1-fold variations, respectively. Analyses on the physicochemical properties of BC demonstrate that QYs of 3 BC* and 1 O2 were linked to the optical properties of BC, while the QYs of H2 O2 and · OH were determined by multiple factors including the surface redox characteristics. Further, PPRIs productions from BC follow similar paths and efficiencies compared to those from natural organic matter. The revealed QYs of BC-derived PPRIs establish a key basis for evaluating PPRIs-mediated element cycles and pollutant transformation in natural waters, which are becoming increasingly important in the context of higher BC input from more frequent wildfires and artificial sources. Graphical abstract: Image, graphical abstract